Emergency preparedness by responders at the Penang International Airport - Eh Kiu, Eh Bon (2001)
Nowadays the public is more aware of their safety especially the travelers. It is very important that the airport plan clearly reflect in accordance with the national aviation security programme, responsibility for the evaluation of all potential violent threats, whether they affect aircraft on the tarrnac or in flight, or buildings at the airport. This study was conducted to assess the level of emergency preparedness by the responders at the Penang International Airport pertaining to the security system. The indication of "room for improvement" must be considered and attended to immediately so as to preserve greater security in the near future.